Ideotype of apples with resistance to storage diseases - J. Blažek; H. Opatová; J. Goliáš; I. Homutová (Horticultural Science, 2007)
Upon the completion of a three-year evaluation of natural occurrence of storage diseases within a range of cultivars or advanced selections and a simultaneous assessment of their other characteristics, an apple ideotype has been proposed that could be used in breeding of new cultivars resistant to these diseases. The ideotype combines the potential of apples for long-term storage with higher skin thickness and toughness, a lower production of ethylene, a higher natural content of calcium, a higher content of total phenolic compounds and antioxidant capacity, a higher flesh firmness, and a higher acidity of juice expressed in pH values. For some of these characteristics, threshold values have been suggested in the paper. The genotypes preselected according to these criteria should be chosen on the basis of the final screening with Pezicula alba inoculum test. The result of the inoculation test should be equal to or better than the standard cultivar Gala. Future research is required to determine the feasibility of the ideotype in routine breeding programs.